Modern trends in the development of the problem of insolation and sun protection in architecture and design - Utesheva Гульнур; Efimov Андрей (Рroblems of engineering and professional education, 2023)
The overview of waterproofing of underground buildings and structures are reviewed in this article. Waterproofing measures of underground parts of buildings and structures from the action of surface and groundwater are considered. Principles of waterproofing work are revealed.